TLBO algorithm for the optimum sensor placement in barrel structures - Maksym Grzywiński; Büşra Yakak; Barbaros Atmaca; Tayfun Dede (Budownictwo o Zoptymalizowanym Potencjale Energetycznym)
In civil engineering, structural health monitoring (SHM) involves observing and analyzing a system over time using periodic measurements of the engineering structures themselves. These measurements are made using sensors. This study aims at reducing the total number of sensors needed and to find the optimal sensor placement. The meta-heuristic method named the Teaching-Learning Based Optimization (TLBO) algorithm is preferred. To get modal properties of the barrel structures, the OAPI properties of the SAP2000 program were used. A computer program coded in MATLAB programming was developed to combine the modal analysis of the structure and the optimization process for sensors.